An appropriate tool for entrepreneurial learning in SMEs? The case of the 20Twenty Leadership Programme. (August 2015) - Clifton, Nick; Huggins, Robert; Morgan, Brian; Thompson, Piers
The 20Twenty Leadership Programme was developed by Cardiff Metropolitan University as an executive education programme to be delivered within South Wales to small businesses. It is funded by the European Social Fund, administered by the Welsh European Funding Office and has the key aim of developing small and medium sized enterprises' growth potential via a range of leadership and management skills, including a focus on 'soft' skills. The aim of this paper is to place the 20Twenty Leadership Programme within the wider context of entrepreneurship policy and small and medium sized enterprise training initiatives in particular, and then to examine the rationale and delivery methods of the Programme in relation to these. It also reflects on the Programme's success (or otherwise) to date where possible. Finally, the paper seeks to suggest fruitful areas of further research both in terms of the 20Twenty Leadership Programme itself and also with regard to evaluation in relation to other parallel programmes and to small and medium sized enterprise training initiatives more generally.